Development of Panax notoginseng saponins-loaded orodispersible films: A potential approach to enhance delivery efficacy in older adults - Khanh Van Nguyen, Thu Kim Dang, Ha Thai Pham, Binh Thi Thanh Nguyen, Giang Thi Thu Vu, Hai Thanh Nguyen, Hiep Tuan Tran (Journal of Applied Pharmaceutical Science, 2022)
Panax notoginseng saponins (PNS), a fraction of Chinese herbal medicine P. notoginseng, have shown clinical potential in the management of diabetic and cardiovascular diseases. The oral administration of these saponins was impaired due to their instability in the gastric fluid. In the current study, we developed novel orodispersible films (ODFs) which are intended to deliver the active ingredients at the oral cavity leading to quick and enhanced absorption of PNS. Firstly, five main saponins, R1, Rg1, Re, Rb1, and Rd, were extracted and evaluated using the High Performance Liquid Chromatography method. The obtained saponins were loaded into an ODF composed of Polyvinyl Alcohol, sorbitol, and saponins that was able to disintegrate within 30 seconds. The Fourier Transform Infrared Spectroscopy spectrum showed that the saponins and other ingredients have no interaction and the in vitro drug release indicated that all saponins could be released in 5 minutes suggesting a possibility of using ODFs as an effective carrier for the delivery of PNS.
Keywords: Panax notoginseng saponins, orodispersible film, herbal, fast disintegration, oral cavity.